Internalized TSH receptors en route to the TGN induce local Gs-protein signaling and gene transcription - Amod Godbole (Nature Portfolio, 2017)
Recent investigations suggest that G-protein-coupled receptors (GPCRs) can signal during intracellular trafficking. Here the authors use fluorescence microscopy approaches to directly visualize and investigate functional consequences of GPCR-mediated signaling at the Golgi/trans-Golgi network.